Antimicrobial activity and toxicity of stingless honey hives Melipona rufiventris and Melipona fasciculata: a review (Research, Society and Development, 2020)
Objective: To characterize the importance of stingless bees and studies of antimicrobial activity and toxicity of Melipona rufiventris and Melipona fasciculata honeys. Methodology: Bibliographic review was carried out in the databases: Scientific Electronic Library Online (SciElo), Google Scholar and PubMed. Articles, monographs, dissertations and theses were selected, dated between 2005 and 2020, in English, Portuguese and Spanish. The search was performed using the keywords: honey, toxicity, antimicrobial agents, Melipona rufiventris and Melipona fasciculata. And duplicate, incomplete articles were excluded from the research. Results: Some studies specify the antimicrobial activity of honeys to certain substances, citing hydrogen peroxide, methyl-glyoxal, hydroxymethylfurfural, phenolic acids, flavonoids and defensins, as the main antibacterial and antifungal agents. Regarding the toxic potential, it alludes that the equipment used for the collection and handling of honey are considered the main sources of contamination by pathogenic microorganisms, considerably increasing the microbiological profile. Conclusion: For antimicrobial and antifungal activities, it should be said that they are generally associated with substances such as hydrogen peroxide, methyl-glyoxal, hydroxymethylfurfural, phenolic acids, flavonoids and defensins. In addition, the evidence about the toxic potential of this product is related to the sources of contamination by pathogenic microorganisms.